Sambutan Wakil Presiden RI Pada Dies Natalis Universitas Diponegoro Ke-55 - Boediono (Kementerian Sekretarian Negara RI, 2012)
Sambutan Wakil Presiden RI Pada Dies Natalis Universitas Diponegoro Ke-55